Inclusive school practice High School schools in Macapá/Ap (2017) - Lobo, Géssica dos Anjos (2020)
High school is the last stage of basic education. It promotes education from a human perspective, seeking ethics, intellectual autonomy and criticality. The perspective of inclusive practice originated from a worldwide movement based on human rights. The objective of this work was to analyze how inclusive school practice occurs in high schools in the municipality of Macapá -AP in 2017. The research was carried out using the database of the National Institute of Educational Studies and Research Anísio Teixeira -INEP. Inclusive education in secondary education is hampered by the lack of resources, both monetary and infrastructure, in addition to their poor management. Teachers, although sometimes inserted in continuing education processes, need that training for inclusive education be constant and comprehensive, covering the theoretical and also the practical axis.